Otitis media with effusion in children with cleft palate - Nanbu, Takako; Matsushima, Akemi; Ogahara, Noboru (Pediatric Otorhinolaryngology Japan, 2011)
The present study retrospectively examined the incidence, treatment, and outcome of otitis media with effusion (OME) in 233 children with cleft palate who underwent palatoplasty from 1994 to 2004 at Kanagawa Children's Medical Center, Yokohama. Data on the presence of otitis media with effusion at the first visit and last follow-up and grommet insertion was collected from clinical notes. At the first visit (mean age 10.4 months), OME was found in 298/466 ears (64%) of all cleft palate children, but was found in only 6/30 ears (20%) of submucous cleft palate children. Grommet insertion was performed in 220 ears (47.3%). At the last follow-up (mean age of 80.4 months), patients did not have OME in 365 ears (78.3%), and had OME in 38 ears (8.2%), perforations in 24 ears (5.2%), and grommets in 38 ears (8.2%). OME was not found in 138/220 ears (62.7%) with grommet insertion and 227/245 ears (92.7%) without grommet insertion. Thus, OME was found in 298/466 ears (64.0%) of cleft palate children at the first visit, but it was not found in 365 ears (78.3%) at the last follow-up. At the last follow-up, the incidence of ears without OME was significantly lower in the ears with grommet insertion than in the ears without it. It is not recommended that all children with cleft palate undergo grommet insertion at palatoplasty, but we think that grommet insertion should be performed in cleft palate children in whom OME is persistent.